A study of socio demographic condition of North eastern Bihar - Singh, Niraj K; Singh, B P; Yadava, K.N.S; Singh, Brijesh P (Recent Research in Science and Technology, 2013)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif][if gte mso 9]> <![endif][if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; –> <!–[endif] –> The main objective of this paper is to study the socio-economic and demographic conditions of this flood-prone region of north-eastern Bihar based on the data taken from a primarily conducted sample survey entitled “Migration and Related Characteristics - a Case Study of North-Eastern Bihar” during October 2009 to June 2010. A total of 664 households have been surveyed from the flood affected area of north-eastern Bihar consisting 8 villages of three districts Bhagalpur, Katihar and Purnia. Bivariate analysis and suitable statistical techniques have been applied. Results show that the study area is still backward from the other part of the state as well as the country.